2022
DOI: 10.1093/nar/gkac444
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced nucleosome assembly at CpG sites containing an extended 5-methylcytosine analogue

Abstract: Methylation of cytosine to 5-methylcytosine (mC) at CpG sites is a prevalent reversible epigenetic mark in vertebrates established by DNA methyltransferases (MTases); the attached methyl groups can alter local structure of DNA and chromatin as well as binding of dedicated proteins. Nucleosome assembly on methylated DNA has been studied extensively, however little is known how the chromatin structure is affected by larger chemical variations in the major groove of DNA. Here, we studied the nucleosome formation … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…The availability of a new type of epigenomic information (Dnmt-selective methylation profiles) will facilitate the resolution of many puzzles of how genomic methylation is established and maintained during development, senescence, and disease. In another vein, we found that the deposited tags can render nucleosome repositioning in DNA, 69 which opens new avenues in manipulating epigenetic processes in live cells.…”
Section: Discussionmentioning
confidence: 96%
“…The availability of a new type of epigenomic information (Dnmt-selective methylation profiles) will facilitate the resolution of many puzzles of how genomic methylation is established and maintained during development, senescence, and disease. In another vein, we found that the deposited tags can render nucleosome repositioning in DNA, 69 which opens new avenues in manipulating epigenetic processes in live cells.…”
Section: Discussionmentioning
confidence: 96%
“…To analyse DNA binding of recombinant AT Baz2B -hooks and BRD BRG1 and BRD Baz2B , EMSAs were performed as described in ( 21 ) and ( 61 ), respectively. To test bromodomain binding to DNA, the Widom 147 bp DNA substrate was used and it was prepared as described ( 62 ).…”
Section: Methodsmentioning
confidence: 99%
“…[126][127][128][129][130] There is a general tendency for reduced twist and increased roll angles when C is substituted by mC or hmC, probably due to a steric hindrance of the cytosine 5-substituent. 129 hmC results in a 0.8 Å (4.5%) widening of the major groove at the site of modification, 127 similarly to mC or other C5 modifications, 131 reviewed in. 132 The hydroxymethyl moiety extends into the major groove (Fig.…”
Section: Single-molecule Long Read Biophysical Detectionmentioning
confidence: 99%
“…129,136 Finally, there can be differences between effects of solitary hmC modifications and their cooperative impact in larger clusters. 129,131…”
Section: Structure and Interactions Of Hmc-dnamentioning
confidence: 99%
See 1 more Smart Citation